2013
DOI: 10.1590/1414-431x20132770
|View full text |Cite
|
Sign up to set email alerts
|

H1 but not H2 histamine antagonist receptors mediate anxiety-related behaviors and emotional memory deficit in mice subjected to elevated plus-maze testing

Abstract: This study investigated the role of H1 and H2 receptors in anxiety and the retrieval of emotional memory using a Trial 1/Trial 2 (T1/T2) protocol in an elevated plus-maze (EPM). Tests were performed on 2 consecutive days, designated T1 and T2. Before T1, the mice received intraperitoneal injections of saline (SAL), 20 mg/kg zolantidine (ZOL, an H2 receptor antagonist), or 8.0 or 16 mg/kg chlorpheniramine (CPA, an H1 receptor antagonist). After 40 min, they were subjected to the EPM test. In T2 (24 h later), ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…We found a U-shaped dose-response relationship between CLOZ and anxiety. One possible explanation for this comes from the fact that 5-HT 2A (see above) and H 1 receptor blockade has anxiogenic effects in the elevated plus-maze (Serafim et al, 2013 ) while α 1 receptor antagonism is rather anxiolytic in this test (Komaki et al, 2014 ; Skelly and Weiner, 2014 ; Rasmussen et al, 2017 ). The observed net effect on anxiety could thus be a function of the differential contribution of these receptor types depending on CLOZ binding.…”
Section: Discussionmentioning
confidence: 99%
“…We found a U-shaped dose-response relationship between CLOZ and anxiety. One possible explanation for this comes from the fact that 5-HT 2A (see above) and H 1 receptor blockade has anxiogenic effects in the elevated plus-maze (Serafim et al, 2013 ) while α 1 receptor antagonism is rather anxiolytic in this test (Komaki et al, 2014 ; Skelly and Weiner, 2014 ; Rasmussen et al, 2017 ). The observed net effect on anxiety could thus be a function of the differential contribution of these receptor types depending on CLOZ binding.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with Serafim et al (10) who demonstrated the anxiogenic effect of CPA in mice at various doses. It was proposed that the H1 receptor antagonists supress acetylcholine release from the ventral striatum; furthermore, acetylcholine is associated with anxiety-like behaviours in rodents (10).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the anxiolytic and antidepressant effect of CPA was evident in animal models (8,9). However, these results have been challenged by previous findings (10) in which CPA was demonstrated to exert anxiogenic effects in mice.…”
Section: Introductionmentioning
confidence: 92%
“…[ 16 ] Serafim et al . [ 17 ] reported an important role of H 1 and not H 2 receptors in anxiety-like behavior. H 1 receptor blockers showed increase in brain levels of noradrenaline and 5-HT and no effect on DA.…”
Section: Discussionmentioning
confidence: 99%